2021
DOI: 10.1136/postgradmedj-2021-140376
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of the APACHE II score and mortality for different types of intensive care unit patients

Abstract: ObjectivesFind the discriminant and calibration of APACHE II (Acute Physiology And Chronic Health Evaluation) score to predict mortality for different type of intensive care unit (ICU) patients.MethodsThis is a cohort retrospective study using secondary data of ICU patients admitted to Siloam Hospital of Lippo Village from 2014 to 2018 with minimum age ≥17 years. The analysis uses the receiver operating characteristic curve, student t-test and logistic regression to find significant variables needed to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The predictive value of the baseline lactate level plus the APACHE II score was higher than that of the lactate clearance at 24 hrs, and the APACHE II score was more valuable than the lactate level at baseline for predicting the prognosis of critically ill patients with abnormal lactate levels. A clinical trial showed that the mortality rate increased as the APACHE II score increased, and the APACHE II score had a better value for predicting patient prognosis [36]. In this study, the results showed that although the AUC of the APACHE II score for predicting prognosis was higher (0.838), its sensitivity and specificity were somewhat poor (81.0 and 75.9%, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…The predictive value of the baseline lactate level plus the APACHE II score was higher than that of the lactate clearance at 24 hrs, and the APACHE II score was more valuable than the lactate level at baseline for predicting the prognosis of critically ill patients with abnormal lactate levels. A clinical trial showed that the mortality rate increased as the APACHE II score increased, and the APACHE II score had a better value for predicting patient prognosis [36]. In this study, the results showed that although the AUC of the APACHE II score for predicting prognosis was higher (0.838), its sensitivity and specificity were somewhat poor (81.0 and 75.9%, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…However, APACHE II and SAPS II scoring predictions are very complex, requiring multiple variables to calculate their score ( 104 ). Their cut-offs, sensitivity, and specificity for predicting the mortality risk of ICU patients vary with patient populations ( 79 ). In addition, they are weak to measure organ dysfunction ( 105 ) and are affected by lead-time bias and treatment ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the subgroup analysis of strains, we evaluated studies that used only Lactobacillus rhamnosus GG as probiotics and mixed strains as probiotics. Moreover, we divided the subgroups into highseverity of illness and low-severity illness groups according to the Acute Physiology And Chronic Health Evaluation (APACHE) II score of 20 at baseline or Simplified Acute Physiology Score (SPSA) II score of 35 at baseline (10,(79)(80)(81). According to the ROB results, the study was divided into high-quality (only low ROB) and low-quality (moderate and high ROB) groups.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Our research found that the expression level of TRIM7 in PBMCs of patients with non-septic-infection was lower than that of normal controls, while the expression level of TRIM7 in PBMCs of patients with sepsis was lower than that of patients with non-septic-infection. At the same time, the expression of TRIM7 was negatively correlated with disease severity scores including SOFA [ 27 ], APACHE II score [ 28 ], and inflammation-related indicators including WBC, CRP, PCT, TNF-α, and IL-6. The expression of TRIM7 in PBMCs of individuals with infection is closely related to its biological role in affecting inflammatory response through regulating the TLR4 pathway, and its change trend is consistent with the results of our previous cell experiments.…”
Section: Discussionmentioning
confidence: 99%